2012
DOI: 10.1074/jbc.m112.367656
|View full text |Cite
|
Sign up to set email alerts
|

Raf-1 Kinase Inhibitory Protein (RKIP) Mediates Ethanol-induced Sensitization of Secretagogue Signaling in Pancreatic Acinar Cells

Abstract: Background:The molecular mechanism by which ethanol (EtOH) sensitizes pancreatic acinar cells to secretagogue stimulation is largely undefined. Results: Ethanol stimulates PKC-dependent RKIP phosphorylation, and RKIP ablation prevents EtOH-induced sensitization of secretagogue Ca 2ϩ signaling and aberrant chymotrypsin activation. Conclusion: RKIP mediates the cytotoxic effects of EtOH on pancreatic acinar cells. Significance: Modulation of RKIP expression may have therapeutic utility in the prevention or treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
(59 reference statements)
0
5
0
1
Order By: Relevance
“…The association between ethanol (EtOH) consumption and pancreatitis has been well‐established. In an elegant study, EtOH has been shown to induce the sensitization of secretagogue Ca 2+ signaling in pancreatic aciner cells and to induce subsequent adverse reactions, resulting in pancreatitis (Kim et al, 2012c). Kim et al showed that EtOH induced the PKC‐dependent phosphorylation of RKIP.…”
Section: Clinical Significance Of Rkip and Prkip Perturbationmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between ethanol (EtOH) consumption and pancreatitis has been well‐established. In an elegant study, EtOH has been shown to induce the sensitization of secretagogue Ca 2+ signaling in pancreatic aciner cells and to induce subsequent adverse reactions, resulting in pancreatitis (Kim et al, 2012c). Kim et al showed that EtOH induced the PKC‐dependent phosphorylation of RKIP.…”
Section: Clinical Significance Of Rkip and Prkip Perturbationmentioning
confidence: 99%
“…These data highlight RKIP as a pivotal mediator of EtOH cytotoxic effect on pancreatic aciner cells. Therefore, the inhibition of RKIP expression may be utilized as a therapeutic treatment strategy to prevent alcohol‐related pancreatitis, which, if left untreated may eventually develop into cancer (Kim et al, 2012c). This study also suggests an important role for p‐RKIP in Ca 2+ homeostasis, which may be significantly relevant to other diseases associated with Ca 2+ perturbations.…”
Section: Clinical Significance Of Rkip and Prkip Perturbationmentioning
confidence: 99%
“…HCT116 cells were infected at a multiplicity of infection (MOI) of 3 with hexadimethrine bromide (8 μg/mL). Transduced cells were selected and maintained in McCoy's 5A media supplemented with 10% (vol/vol) FBS and puromycin (2 μg/mL) (45). To overexpress CBS in NCM356 cells, gene transfer was accomplished using an adenovirus at a MOI of 10, with a green fluorescent protein-expressing adenovirus used as a control (46).…”
Section: Methodsmentioning
confidence: 99%
“…Under certain inflammatory conditions, including chronic pancreatitis 13 and metabolic disorders, 14 phosphorylation of RKIP occurs through protein kinase C (PKC), phosphatidyl inositol-3 kinase (PI3K) or other pathways. When induced by protein PKC, phosphorylation occurs at the Ser153 residue, inducing a conformational change in the ligand binding pocket.…”
Section: Rkip Contribution To Pro-inflammatory Signaling (Table 2)mentioning
confidence: 99%